2014
DOI: 10.1016/j.wneu.2014.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Early Postoperative High-Resolution Volumetric Magnetic Resonance Imaging After Transsphenoidal Pituitary Tumor Surgery

Abstract: Objective Controversy exists over the utility of early post-operative magnetic resonance imaging (MRI) after transsphenoidal pituitary surgery for macroadenomas. We investigate whether valuable information can be derived from current higher resolution scans. Methods Volumetric MRI scans were obtained in the early (<10 days) and late (>30 days) post-operative periods in a series of patients undergoing transsphenoidal pituitary surgery. The volume of the residual tumor, resection cavity, and corresponding visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Early postoperative MRI scans are performed routinely in 36 centres (13.4%), for selected cases in 120 centres (47.2%), while 96 centres (37.8) do not perform early MR scanning at all. The role of early imaging is often questioned, mainly because of di culty in identifying residual tumours and interpreting early postoperative changes, such as persistent cavity enlargement, accumulation of haemorrhagic material and fat packing [27]. Stofko et al showed that early postoperative MRI scan provides accurate and reliable information regarding residual tumor presence compared with reconstruction and packing materials with sensitivity 100% and speci city 97.9% [33].…”
Section: Postoperative Imagingmentioning
confidence: 99%
“…Early postoperative MRI scans are performed routinely in 36 centres (13.4%), for selected cases in 120 centres (47.2%), while 96 centres (37.8) do not perform early MR scanning at all. The role of early imaging is often questioned, mainly because of di culty in identifying residual tumours and interpreting early postoperative changes, such as persistent cavity enlargement, accumulation of haemorrhagic material and fat packing [27]. Stofko et al showed that early postoperative MRI scan provides accurate and reliable information regarding residual tumor presence compared with reconstruction and packing materials with sensitivity 100% and speci city 97.9% [33].…”
Section: Postoperative Imagingmentioning
confidence: 99%
“…Therefore, MRI is usually performed 3–6 months after surgery, when most of the postoperative changes have disappeared [7, 52, 109, 110]. According to recent studies, early MRI has nowadays significantly higher sensitivity and specificity for detecting residual tumor than previously reported, providing valuable information to guide future care [111, 112]. The intervals for further radiological follow-up should be decided based on individual characteristics such as residual tumor size and distance from the optic chiasm.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies using modern MR techniques that are now the standard of care in pituitary imaging have indicated that EPO MRI is very accurate, with efficacy similar to that of LPO MRI at 3 months. 29,34 However, these studies used LPO MRI as the gold standard by which EPO MRI was judged, and neither study addressed the consideration that EPO MRI may, in fact, be more accurate than LPO MRI. As a result, neither study used an external gold standard, such as reresection or long-term follow-up, to determine whether LPO MRI findings were accurate.…”
Section: Figmentioning
confidence: 99%
“…2,17,18,21,31 More recent studies have suggested that EPO MRI is as accurate as late postoperative (LPO) MRI at 3 months. 29,34 However, these studies have failed to compare both imaging tests against an independent gold standard.…”
mentioning
confidence: 99%